Comparative Clinical and Laboratory Assessment of the Effectiveness of Rehabilitation Therapy in Patients with Osteoarthritis of the Knee Joints - O. A. Rechkunova; T. V. Chernysheva; I. A. Krivotulova; N. V. Sharapova (Архивъ внутренней медицины)
Purpose. To evaluate the effectiveness of the course administration of an ozone-oxygen mixture into the periarticular tissues of the knee joint in patients with osteoarthritis who underwent total arthroplasty of one of the joints and to study the effect of this technique on the state of lipid peroxidation and the antioxidant defense system of the body relative to traditional methods of restorative treatment.Materials and methods. The study included 120 patients with bilateral gonarthrosis after endoprosthetics of one of the knee joints. The average age of the patients was 60 [46; 76] years. Depending on the method of rehabilitation treatment, the patients were divided into 3 equal groups (n=40): the 1st group was prescribed periarticular subcutaneous ozone therapy in combination with therapeutic exercise, the 2nd group — magnetotherapy and electrophoresis on the knee joint area in combination with therapeutic exercise, and 3rd group — only the complex of therapeutic exercise. In all patients, before and after rehabilitation treatment (after 14 days and 3 months), the clinico-functional status was assessed using the Western Ontario and McMaster Universities Osteoarthritis Index scale and the indicators of the intensity of the free radical oxidation processes and the activity of antioxidant protection were studied.Results. A detailed analysis of the clinico-functional state among patients of group 1 relative to group 2 and 3 revealed the best “long-term” result: a marked decrease in pain (p <0.05, p <0.0001), stiffness (p <0.05, p <0.0001), limitations physical activity (p <0.01, p <0.0001) due to the improvement of the main indicators of the antioxidant protection system against the background of ongoing therapy: catalase (p <0.01) and superoxide dismutase (p <0.01).Conclusion. The use of periarticular ozone therapy makes it possible to achieve a more stable positive effect in patients after total knee arthroplasty relative to traditional methods of restorative treatment due to its pronounced antioxidant effect aimed at stabilizing the processes of lipid peroxidation.